Proceedings of the 9th Annual Conference Companion on Genetic and Evolutionary Computation 2007
DOI: 10.1145/1274000.1274018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of binary differential evolution in dynamic environments

Abstract: Many real-world optimization problems are dynamic in nature. The interest in the Evolutionary Algorithms (EAs) community in applying EA variants to dynamic optimization problems has increased greatly. Differential Evolution (DE) belongs to the group of evolutionary algorithms which operate in continuous search spaces. DE has been successfully applied to many stationary problem domains. Recently there has been some research into applying DE to dynamic optimization problems too. Many real-world problems consist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…We replace our binary differential evolution in MOBDE by using the binary DE, BDE and BDEAIS [33,34,39]. That is to say, all of these methods use the same multiobjective framework to conduct a fair comparison.…”
Section: Discussion and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…We replace our binary differential evolution in MOBDE by using the binary DE, BDE and BDEAIS [33,34,39]. That is to say, all of these methods use the same multiobjective framework to conduct a fair comparison.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…The datasets are classified by LIBSVM based on LOOCV. We compared our method with some binary differential evolution algorithms: binary DE [33], binary differential evolution (BDE) [34], binary differential evolution with artificial immune system (BDEAIS) [39], binary particle swarm optimization (BPSO) [40], binary genetic algorithm (BGA) [41] and binary estimation distribution algorithm (BEDA) [42]. In this paper, we replace these methods with our binary method and then compare our method to show the effective of the algorithm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that Differential evolution algorithm (DE) [11] is be a simple and powerful algorithm for continuous function optimization, not even in static [12] but also in dynamic environments [7,[13][14][15]. Moreover, DynDE [7], which to the best of our knowledge is the best-performing differential evolution algorithm for dynamic optimization problems, produces competitive results compared to other dynamic optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%